(untitled) (Journal “Crop Production, Selection And Seed Production, Fruit And Vegetable Growing”, 2025)
Formulation of the problem. Safflower (Carthamus tinctorius L.) is an oilseed crop characterized by high drought resistance and adaptability to arid climatic conditions. In the forest-steppe zone of Ukraine, increased aridity and depletion of groundwater reserves significantly limit its productivity. The choice of the main soil cultivation system directly affects the hydrothermal properties of the soil and crop yields, but there is still insufficient research in the conditions of the Kharkiv region. The purpose of the research. The study aimed to assess the impact of different tillage systems on soil water regime, growth, and yield formation of safflower under conditions of typical black soils in Kharkiv region. Research methods. The research was conducted at the Vidrodzhennia private enterprise in the Krasnohrad district, where black soil with a humus content of 4.8–5.0% and a neutral soil solution reaction prevail. The research was conducted in a grain-steam-row crop rotation system, in which safflower was sown after winter wheat. The Dobrynya variety of safflower was used in the experiment. The experiment was designed according to the principle of systematic variation in accordance with methodological recommendations. The studied variants of basic soil cultivation for safflower cultivation were: plow plowing PLN-5-35 (control) and non-plow chisel cultivation AGR-1.7 to a depth of 25–27 cm, as well as disc harrowing BDT-7 to a depth of 18–20 cm. The growing season was characterized by abnormally high temperatures (+3.4°C above the long-term average) and critically low precipitation (76 mm in April–September, which is 191 mm below normal). This led to a deficit of productive moisture and increased soil compaction. Research results. The results of the study showed that the moisture content of the black soil varied depending on the phase of safflower development and the depth of the arable layer. The upper horizon (0–10 cm) was most prone to drying out, while the lower horizon (20–30 cm) retained moisture the longest. Plowing provided good conditions for moisture accumulation in the spring, but in drought conditions, it contributed to rapid drying of the upper layer and compaction of the subsoil horizon (up to 29.1 kg/cm²). Chiseling, on the contrary, allowed for better moisture retention during the growing season due to the absence of a plow pan and the preservation of capillary water conductivity in the soil. Disc harrowing provided only superficial loosening, which led to rapid moisture loss and critical compaction of deeper horizons (up to 28.6 kg/cm²). The yield of safflower depended on the type of tillage: with chisel plowing, it was 1.01 t/ha, with plowing – 0.93 t/ha, and with disc harrowing – 0.74 t/ha. Economic analysis showed that chisel plowing was the most profitable (60%), while plowing and disc harrowing provided lower rates (49% and 48%, respectively). This is explained by the optimal ratio between costs and yield levels with chisel plowing. Conclusions. Thus, in the arid conditions of the forest-steppe zone of the Kharkiv region, the most effective method of primary soil cultivation for safflower is chisel plowing, which provides a better balance between moisture retention, soil loosening, and structural stability, allowing for higher productivity and economic efficiency of production.